Are Humans Prepared to Detect, Fear, and Avoid Snakes? The Mismatch Between Laboratory and Ecological Evidence - Coelho, Carlos M.; Suttiwan, Panrapee; Faiz, Abul M.; Ferreira-Santos, Fernando; Zsido, Andras N. (Frontiers in Psychology, 2019)
Since Seligman's 1971 statement that the vast majority of phobias are about objects essential to the survival of a species, a multitude of laboratory studies followed, supporting the finding that humans learn to fear and detect snakes (and other animals) faster than other stimuli. Most of these studies used schematic drawings, images, or pictures of snakes, and only a small amount of fieldwork in naturalistic environments was done. We address fear preparedness theories, and automatic fast detection data from mainstream laboratory data and compares it with ethobehavioural information relative to snakes, predator-prey interaction, and snakes’ defensive kinematics strikes in order to analyse their potential matching. From this analysis four main findings arose, namely that: 1) Snakebites occur when people are very close to the snake and are unaware or unable to escape the bite; 2) Human visual detection and escape response is slow compared to the speed of snake strikes; 3) In natural environments, snake experts are often unable to see snakes existing nearby; 4) animate objects in general capture more attention over other stimuli and dangerous but recent objects in evolutionary terms are also able to be detected fast. The issues mentioned above pose several challenges to evolutionary psychology-based theories expecting to find special-purpose neural modules. The older selective habituation hypothesis (Schleidt, 1961), that prey animals start with a rather general predator image from which specific harmless cues are removed by habituation might deserve reconsideration.